Redes neurais artificiais aplicadas na caracterização e predição de regiões promotoras - Silva, Scheila de Avila e (Universidade do Vale do Rio do Sinos, 2007)
The promoter region is localized few base pairs before the gene region. It is responsible by initiate the gene expression process, thus, it plays a regulatory role. The study about the gene expression regulation is a great area, since it can assist in the comprehension of complex metabolic network presented by several organisms and, because the difference between two different species is how and when your genes are turn off and turn on than your structure. The computational methods to gene prediction have a good accuracy, but this is not achieved in the promoter prediction. This difficulty occurs because the length of promoter and the degenerate pattern presented, thus the results presented a great number of false positives. This work aims employed Neural Networks to promoter prediction and recognition of Escherichia coli by two approaches: whit the orthogonal codification and stability values of the promoter sequence. For characterization, realize the extraction rules of type if … then. The results in this
Keywords: bioinformática; biologia molecular; computação; genética; rede neural; rede neural artificial; neural network; prediction; promoters prokaryotic; Ciências Exatas e da Terra